Food poisoning outbreak cases among school children in Terengganu year 2016 and its associated factors - Abdullah, Nur Baizura Aini (2018)
Background: Food poisoning is a public health problem in Malaysia and is in the top five communicable diseases in Malaysia. Terengganu had also shown increasing trend of food poisoning involving school children. Objective: This study aimed to determine the proportion of food poisoning cases involving school children in Terengganu in year 2016 and to determine the associated factors of food poisoning outbreak involving school children in Terengganu in year 2016. Methodology: This was a cross–sectional study using secondary data of 21 food poisoning outbreaks collected among school children in Terengganu that involved in food poisoning outbreak at school in year 2016. The data were obtained from Borang Siasatan Keracunan Makanan’ (FWBD/KRM/BG 001) Pindaan 2008 and final outbreak report from eWabak system. Result: The proportion of food poisoning outbreak involving school children in Terengganu in year 2016 was 63.6%. Ministry of Education schools had contributed to 95.3% of food poisoning outbreak cases and 81% occurred at secondary schools. Most of the food poisoning outbreak (57.1%) occurred at schools located in rural district. Poultry was the most food vehicle related to school food poisoning outbreak with the proportion of 61.9%. The commonest microbial etiological agent was Salmonella spp. (52.4%) and 57.1% of critical control point involved was inadequate cooking and reheating. Schools that were located in rural district (aOR=1.668; 95% CI: 1.355,2.055; p<0.001), non-MOE school (aOR = 3.621; 95% CI: 2.368, 5.537; p<0/001), were the factors at higher risk to involve in school food poisoning outbreak. Meanwhile, for food vehicle,poultry (aOR= 0.384; 95% CI: 0.180,0.819; p=0.013), red meat (aOR=0.327; 95% CI: 0.181,0.589; p<0.001) and rice/grain (aOR= 0.216; 95% CI: 0.083,0.563; p= 0.002) are more protective than eggs that were associated with the occurrence school food poisoning outbreak in Terengganu year 2016. The CCP factors were all not significant in our studies. Conclusion: Food poisoning among school children in Terengganu had been associated with non-modifiable factors such as school category (MOE & non-MOE school) and school district location and modifiable factors such as food vehicles and critical control points involved. In preventing food poisoning in school, health education need to be strengthened on food safety, proper food handling, strict hygiene practice, and clean canteen environment during food preparations.